Geschichte der Pädagogik im Curriculum der Lehrerausbildung für Grund- und Bürgerschulen (tschechisch-deutscher Vergleich: 1918-1939) - eine wissenschaftliche Disziplin im Dienste des Volkes, des Fortschrittes und der Sozialreform) - Tomáš Kasper (Charles University, 2018)
Abstract: The article focuses on the analysis of course books concerning the history of pedagogy used in the interwar period at the Czech and German Teachers' Institutions. Based on the analysis, there is pointed out the role of the subject concerning the history of pedagogy in the given period in the framework of the teachers' training. The analysis is set into the wider context of the development concerning pedagogical thinking and its reflection in the Czech and German pedagogical debate at the turn of the 19th and 20th centuries in the Czech lands of the monarchy and the fi rst half of the 20th century in the interwar Czechoslovakia. The analysis not only points to a different grasp of the historical reflection of pedagogical thinking in both national and cultural camps, but also points to common features in the development of the discipline. These are mainly shown in its functional character, when the history of pedagogy was a discipline supporting the national emancipation of both nations, and they were part of a wider debate concerning reform of the society. Keywords: history of education, teachers' institutes, course books, teachers' training, Czechoslovakia, Czech Lands and the Habsburg Monarchy.